An Environmental audit of Suame Magazine - Wiredu, Abbas Dankwa (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the award of Master of Science degree in Environmental Resources Management.